Expression Profile Analysis to Identify Circular RNA Expression Signatures in Muscle Development of Wu'an Goat Longissimus Dorsi Tissues - Zhou, Zuyang; Li, Kunyu; Liu, Jiannan; Zhang, Hui; Fan, Yekai; Chen, Yulin; Han, Haiyin; Yang, Junqi; Liu, Yufang (Frontiers in Veterinary Science, 2022)
The growth and development of skeletal muscle is a physiological process regulated by a variety of genes and signaling pathways. As a posttranscriptional regulatory factor, circRNA plays a certain regulatory role in the development of animal skeletal muscle in the form of a miRNA sponge. However, the role of circRNAs in muscle development and growth in goats is still unclear. In our study, apparent differences in muscle fibers in Wu’an goats of different ages was firstly detected by hematoxylin-eosin (HE) staining, the circRNA expression profiles of longissimus dorsi muscles from 1-month-old (mon1) and 9-month-old (mon9) goats were screened by RNA-seq and verified by RT–qPCR. The host genes of differentially expressed (DE) circRNAs were predicted, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes analyses (KEGG) of host genes with DE circRNAs were performed to explore the functions of circRNAs. The circRNA-miRNA-mRNA networks were then constructed using Cytoscape software. Ten significantly differentially expressed circRNAs were also verified in the mon1 and mon9 groups by RT–qPCR. Luciferase Reporter Assay was used to verify the binding site between circRNA and its targeted miRNA. The results showed that a total of 686 DE circRNAs were identified between the mon9 and mon1 groups, of which 357 were upregulated and 329 were downregulated. Subsequently, the 467 host genes of DE circRNAs were predicted using Find_circ and CIRI software. The circRNA-miRNA-mRNA network contained 201 circRNAs, 85 miRNAs, and 581 mRNAs; the host mRNAs were associated with “muscle fiber development” and “AMPK signaling pathway” and were enriched in the FoxO signaling pathway. Competing endogenous RNA (ceRNA) network analysis showed that novel_circ_0005314, novel_circ_0005319, novel_circ_0009256, novel_circ_0009845, novel_circ_0005934 and novel_circ_0000134 may play important roles in skeletal muscle growth and development between the mon9 and mon1 groups. Luciferase Reporter Assay confirmed the combination between novel_circ_0005319 and chi-miR-199a-5p, novel_circ_0005934 and chi-miR-450-3p and novel_circ_0000134 and chi-miR-655. Our results provide specific information related to goat muscle development and a reference for the goat circRNA profile.